Measurement of Voice Onset Time in Maxillectomy Patients. (20th January 2014) - Hattori, Mariko; Sumita, Yuka I.; Taniguchi, Hisashi
Abstract : Objective speech evaluation using acoustic measurement is needed for the proper rehabilitation of maxillectomy patients. For digital evaluation of consonants, measurement of voice onset time is one option. However, voice onset time has not been measured in maxillectomy patients as their consonant sound spectra exhibit unique characteristics that make the measurement of voice onset time challenging. In this study, we established criteria for measuring voice onset time in maxillectomy patients for objective speech evaluation. We examined voice onset time for /ka/ and /ta/ in 13 maxillectomy patients by calculating the number of valid measurements of voice onset time out of three trials for each syllable. Wilcoxon's signed rank test showed that voice onset time measurements were more successful for /ka/ and /ta/ when a prosthesis was used (Z = − 2.232, P = 0.026 and Z = − 2.401, P = 0.016, resp.) than when a prosthesis was not used. These results indicate a prosthesis affected voice onset measurement in these patients. Although more research in this area is needed, measurement of voice onset time has the potential to be used to evaluate consonant production in maxillectomy patients wearing a prosthesis.